Effect of an Educational Program for Patients Post Coronary Artery Bypass Surgery on the Compliance with Symptoms Management Strategies - Gehan Karawan Sayed Sallam; Kamelia Fouad Abdalla; Sara Fathi Mahmoud (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Patients undergoing CABG often experience a varied series of discomfort symptoms posthospital dischargeinclude ;shortness of breath, chest pain or angina pain, incisional pain, atrial fibrillationfatigue, leg swelling, sleep quality, loss of appetite, anxiety and depression.Specific educational programregarding symptoms management strategies (SMS) are used to improve patient outcome, therefore patients’compliance with this programis very essential to relief, manage it. Aim: to evaluate the effect of aneducational program for patients post CABS on the compliance with (SMS). Design: a quasi-experimentaldesign. Setting: conducted at outpatient clinics in Cardio Thoracic Academy at Ain Shams Hospital. Subject:a purposive sample of (150) patients post CABG were recruited. Tools: demographic,medical data, CardiacSymptoms Survey (CSS) and compliance scale are used. Results: The subjects were complaint towards(SMS) pre-program (12.7%) changed to (83.3%) post program. As evidence, 53.3% of the subjects who hadsever level of perception of symptoms pre, changed to 5.3% post. Moreover, (62.7%, 59.4% respectively) ofthe subjects who had sever level of frequency, severity of symptoms pre changed to (4 %, 2.7% respectively)post. In addition, (57.3% respectively) of the subjects who had sever level of interference with physicalactivity,enjoyment of life pre, changed to (4%,4% respectively) post.Conclusion: Educational programshowed positive effect on the subjects experienced discomfort symptoms post CABG and their compliancetowards the management strategies.